Pengaruh Religiusitas dan Citra Bank Syariah terhadap Minat Menabung melalui Bank Syariah di Sidoarjo - Revonnarta, Ervanda; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2021)
Asset, financing and third-party fund of bank were increasing in past three years. But, it was not followed by the increase of market share in national banking market. It means that peoples interest in islamic banking still low. This study aims to know whether religiosity and islamic bank image influence saving intention to islamic bank in Sidoarjo. This study is a quantitative study. Using validation test and reliability test for instrument testing, classic assumption testing, multiple linear regression testing and hypothesis test consisting of partial test, simultaneously test and R squared test. The result of this study explains that religiosity and islamic bank image are influencing saving intention to islamic bank in Sidoarjo in both partial and simultaneously way. Variable of religiosity and islamic bank image have the strength to influence saving intention to islamic bank in Sidoarjo by 72,7%.